Study of the Influence of Nanoparticle Reinforcement on the Mechanical and Tribological Performance of Aluminum Matrix Composites—A Review - Varun Singhal; Daksh Shelly; Abhishek Saxena; Rahul Gupta; Vipin Kumar Verma; Appurva Jain (Lubricants)
This study investigates the influence of nano-sized reinforcements on aluminum matrix composites’ mechanical and tribological properties. Microstructural analysis revealed that introducing nanoparticles led to grain refinement, reducing the grain size from 129.7 μm to 41.3 μm with 2 wt.% TiO2 addition. Furthermore, ultrasonic-assisted squeeze casting of AA6061 composites reinforced with TiO2 and Al2O3 resulted in a 52% decrease in grain size, demonstrating nano-reinforcements’ effectiveness in refining the matrix structure. Despite these advantages, the high surface energy of nanoparticles causes agglomeration, which can undermine composite performance. However, ultrasonic-assisted stir casting reduced agglomeration by approximately 80% compared to conventional stir casting, and cold isostatic pressing improved dispersion uniformity by 27%. The incorporation of nano-reinforcements such as SiC, Al2O3, and TiC significantly enhanced the material properties, with hardness increasing by ~30% and ultimate tensile strength improving by ~80% compared to pure Al. The hardness of nano-reinforced composites substantially rose from 83 HV (pure Al) to 117 HV with 1.0 vol.% CNT reinforcement. Additionally, TiC-reinforced AA7075 composites improved hardness from 94.41 HB to 277.55 HB after 10 h of milling, indicating a nearly threefold increase. The wear resistance of Al-Si alloys was notably improved, with wear rates reduced by up to 52%, while the coefficient of friction decreased by 20–40% with the incorporation of graphene and CNT reinforcements. These findings highlight the potential of nano-reinforcements in significantly improving the mechanical and tribological performance of n-AMCs, making them suitable for high-performance applications in aerospace, automotive, and structural industries.